2019
DOI: 10.1111/ppc.12395
|View full text |Cite
|
Sign up to set email alerts
|

LGBT friendly healthcare providers’ tobacco treatment practices and recommendations

Abstract: Purpose This study aimed to describe lesbian, gay, bisexual, and transgender (LGBT) friendly providers’ (1) smoking cessation recommendations to LGBT patients and (2) tobacco treatment practices for transgender patients. Design and Methods In‐depth, semistructured phone interviews were conducted with 13 healthcare providers. Findings Four overarching themes emerged: (1) providing tobacco treatment services for LGBT patients; (2) barriers to LGBT smoking cessation; (3) prescribing practices for transgender indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…A study focused on LGBT-friendly providers’ recommendations for tobacco treatment identified community outreach as an important step towards providing LGBT-tailored tobacco treatment services. 19 Our results align with this study, showing that SUD treatment facilities with community outreach are more likely to have an LGBT-tailored program.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…A study focused on LGBT-friendly providers’ recommendations for tobacco treatment identified community outreach as an important step towards providing LGBT-tailored tobacco treatment services. 19 Our results align with this study, showing that SUD treatment facilities with community outreach are more likely to have an LGBT-tailored program.…”
Section: Discussionsupporting
confidence: 90%
“…17 Providing programs tailored for LGBT individuals may reduce the impact of SUDs on this population. 4,5,[18][19][20][21][22][23] According to the National Survey of Substance Abuse Treatment Services (N-SSATS) 2020, approximately 24% of all SUD treatment facilities have a LGBT-tailored program. 24 On a policy level, LGBT-friendly state-level policies are associated with an increase in the proportion of tailored LGBT programs across mental health and SUD treatment facilities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are gaps in the implementation of clinical best practices by providers in LGBT-serving health centers. 30,34 In supplemental analyses (results not shown), we found that bisexual adults and sexual minority women were less likely to have health insurance. In addition, prior evidence suggests that sexual minority adults have fewer economic resources due to job selection and employment discrimination.…”
Section: Discussionmentioning
confidence: 83%